2003
DOI: 10.1046/j.1365-2516.2003.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited bleeding disorders in Indian women with menorrhagia

Abstract: In order to define the prevalence of haemostatic defects in women presenting with menorrhagia in our region, the coagulation data on women bleeders investigated in the Department of Haematology, AIIMS, were analysed. A total of 337 of the 2200 menorrhagic women investigated were characterized to have an inherited bleeding disorder; 221 of these 337 women presented with menorrhagia alone while 116 also had other associated bleeding manifestations as prolonged bleeding from injury site, ecchymotic patches in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 9 publications
1
33
3
Order By: Relevance
“…Khosla AH et al showed 27 % patients in their study had bleeding disorders [8]. Bevan et al and Saxena R et al showed 13-15 % incidence of thrombocytopenia among girls presented with menorrhagia, which was associated with bruising, petechiae, and mucosal bleeding [20,21]. In our institute, one patient of ITP was managed with blood transfusion and oral progestogen and tranexamic acid.…”
Section: Discussionmentioning
confidence: 80%
“…Khosla AH et al showed 27 % patients in their study had bleeding disorders [8]. Bevan et al and Saxena R et al showed 13-15 % incidence of thrombocytopenia among girls presented with menorrhagia, which was associated with bruising, petechiae, and mucosal bleeding [20,21]. In our institute, one patient of ITP was managed with blood transfusion and oral progestogen and tranexamic acid.…”
Section: Discussionmentioning
confidence: 80%
“…The prevalence of VWD in women presenting with menorrhagia ranges between 10 and 20% in Caucasian women, with a lower (1-2%) prevalence in African-American women [3,8,10,11]. In addition, platelet function defects are reported to be the second common cause of bleeding disorders in women presenting with menorrhagia [8,12]. Single coagulation factor deficiencies have also been reported, although at lower frequency than VWD and platelet function defects [3,6,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, platelet function defects are reported to be the second common cause of bleeding disorders in women presenting with menorrhagia [8,12]. Single coagulation factor deficiencies have also been reported, although at lower frequency than VWD and platelet function defects [3,6,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…9 Single coagulation factor deficiencies, particularly factors XI, VII, and V, have also been identified in studies of women with menorrhagia, although at lower frequencies than von Willebrand's disease and platelet function defects. 3,7,9,15 Menorrhagia occurring during adolescence and perimenopause is presumed to be associated with anovulation or, during perimenopause, also anatomic causes, such as submucosal uterine myoma. 1 The frequency of bleeding disorders in women diagnosed with menorrhagia at the extremes of menstruating age, ie, adolescence and perimenopause, are not known.…”
mentioning
confidence: 99%